Optimization of DNA Extraction and Whole Genome Sequencing for Neisseria gonorrhoeae Isolates and Clinical Samples Using Oxford Nanopore Technology - Wahyono, Daniel Joko; Nastiti, Swasti Arum; Sulaiman, Verawati; Pratama, Wahyu Agung; Setiawaty, Vivi (Elkawnie, 2026)
Abstract: Gonorrhea is a sexually transmitted infection caused by Neisseria gonorrhoeae. Whole-genome sequencing (WGS) is essential for genomic studies of this bacterium to understand its epidemiology and mechanisms of antibiotic resistance. The success of WGS depends on obtaining high-quality genomic DNA. This study aimed to determine optimal DNA concentration and purity from optimized extraction of two isolates from two clinical samples and to achieve optimized genomic data analysis from WGS of both sample types. DNA extraction was performed using the Qiagen DNeasy Blood and Tissue Kit, and WGS was conducted on the GridION platform (Oxford Nanopore Technologies) with Epi2Me software for metagenomic analysis. The results showed that isolates produced higher DNA concentrations with A260/280 ratios of 1.8–2.0, whereas some clinical samples exhibited contamination. Metagenomic analysis revealed Neisseria gonorrhoeae dominance in isolates but low proportions in clinical samples, where other bacteria predominated. In conclusion, optimizing DNA extraction improved DNA quality and enabled valid WGS analysis. Metagenomic analysis revealed that N. gonorrhoeae dominated cultured isolates (~60–72% of reads) but was present at very low levels (<6%) in clinical samples, which were predominantly composed of E. coli, Klebsiella spp., and host DNA. These findings provide practical guidance for optimizing DNA extraction strategies in WGS-based studies of Neisseria gonorrhoeae, particularly for low-biomass clinical samples. They may support more accurate genomic surveillance and antibiotic resistance profiling to inform targeted treatment strategies. Abstrak: Gonore merupakan Infeksi Menular Seksual (IMS) yang disebabkan oleh Neisseria gonorrhoeae. Whole Genome Sequencing (WGS) merupakan metode penting dalam studi genomik bakteri untuk memahami epidemiologi dan mekanisme resistensi antibiotik. Keberhasilan WGS sangat bergantung pada kualitas DNA genomik yang diperoleh. Penelitian ini bertujuan untuk memperoleh nilai optimal konsentrasi dan kemurnian DNA hasil optimasi ekstraksi dari dua isolat pada dua sampel klinis, serta memperoleh hasil optimasi analisis data genomik WGS dari kedua jenis sampel tersebut. Ekstraksi DNA dilakukan menggunakan Qiagen DNeasy Blood and Tissue Kit, sedangkan WGS dilakukan pada platform GridIon (Oxford Nanopore Technologies) dengan perangkat lunak Epi2Me untuk analisis metagenomik. Hasil menunjukkan isolat menghasilkan konsentrasi DNA yang lebih tinggi dengan rasio A260/280 mendekati 1,8–2,0, sementara beberapa sampel klinis menunjukkan adanya kontaminasi. Analisis metagenomik menunjukkan dominasi Neisseria gonorrhoeae pada isolat, namun rendah pada sampel klinis yang didominasi oleh bakteri lain. Berdasarkan hasil tersebut, dapat disimpulkan bahwa optimasi ekstraksi DNA berhasil meningkatkan kualitas DNA dan memungkinkan analisis WGS yang valid. Analisis metagenomik memperlihatkan bahwa N. gonorrhoeae mendominasi isolat (~60–72% bacaan), namun sangat sedikit (<6%) pada sampel klinis, yang didominasi oleh E. coli, Klebsiella, dan DNA inang. Temuan ini memberikan panduan praktis untuk mengoptimalkan strategi ekstraksi DNA dalam studi berbasis WGS pada Neisseria gonorrhoeae, khususnya untuk sampel klinis dengan biomassa rendah, serta dapat mendukung pengawasan genomik yang lebih akurat dan profil resistensi antibiotik untuk memberikan informasi bagi strategi pengobatan yang lebih tepat sasaran.